Quality Assessment of HTA reports: a Critical Appraisal Toolkit within an institutional HTA program. (30th September 2020) - Bossi, E; Tringali, M; Colombo, P; Mazzali, C; Puleo, G; Caruggi, M; Branchi, M; Odone, A
Abstract: Issue: With population aging, increased demand for healthcare and limited availability of economic and human resources, well-functioning and sustainable health systems have to rely on rigorous and evidence-based assessments of complex technologies' clinical effectiveness and safety. The Lombardy Region in Northern Italy has a well-established HTA program that offers technical support to its hospitals' network to produce and to review Health Technology Assessment (HTA) reports. Description of the Problem: To better coordinate the HTA network and to reduce self-referencing of University and Community hospitals, Lombardy Region carried out an intense field training and distance learning from year 2017, with a project aimed at involving health care professionals in an accurate evaluation of technologies in 18 HTA reports. The regional HTA Supporting Centre developed a Toolkit for the critical appraisal of reports and supporting literature to improve the quality of hospital-based reports. Results: In compliance with the regional Law DGR XI/1046 17.12.2018 and the framework proposed, during year 2019 hospitals used the Toolkit to help writing complete and good quality HTA reports on 37 different technologies. With a Public Health resident internship, the Toolkit was revised, extended and then used in 2020 by the hospital's HTA network during the double blinded peer review, mandated by the regional Law DGR XI/2672 16.12.2019, of the year 2019 HTA reports. Detailed results will be presented at the conference. Lessons: We observed an increase in number of HTA reports from 2018 to 2019, a greater language's and format's homogeneity and an improvement in the quality of some reports, which will be submitted to the Regional HTA Committee for appraisal and reimbursement. Key messages: The development and use of a Critical Appraisal Toolkit in an Regional HTA program can help hospitals write complete and good quality HTA reports. A centrally supported quality improvement of distributed assessment activities in a network of hospitals can enhance the production of HTA reports, relevant to the needs of a local healthcare system.